EVALUASI PENGALAMAN PENGGUNA MAHASISWA TERHADAP SISTEM INFORMASI SIASAT: PENDEKATAN DENGAN USER EXPERIENCE QUESTIONNAIRE - Saeful Anwar (Jurnal Ilmu Komputer Ruru, 2025)
This research aims to analyze student user experience on the Satya Wacana Information System (SIASAT) using the User Experience Questionnaire (UEQ). UEQ is a measurement method from the aspect of its use and the aspect of the experience, including a compressive impression using a questionnaire scale. The UEQ has 26 questions that must be filled out by respondents, where the questions cover 6 aspects, including attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. The UEQ questionnaire in this study used data from 54 active SWCU student respondents who understood the use of the Satya Wacana Academic Information System (SIASAT) well. The final results of the tests carried out obtained data for the scale of attractiveness, efficiency, dependability, and stimulation to get a normal evaluation category. Meanwhile, the novelty scale gets a negative evaluation category and the perspicuity scale gets a positive evaluation category. Then for the results of the benchmark evaluation, the majority got the Bad category which includes a scale of attractiveness, efficiency, dependability, stimulation, and novelty. Only one scale that gets the Above Average category (Good Enough) is perspicuity.